2018
DOI: 10.1002/alr.22172
|View full text |Cite
|
Sign up to set email alerts
|

A multi‐institutional review of outcomes in biopsy‐proven acute invasive fungal sinusitis

Abstract: We presented the largest series of AIFS. Further studies are needed to examine the importance of ANC in diagnosis and prognosis. Patients diagnosed with atypical organisms may be at higher risk of death. IST likely improves short-term survival, but prospective studies are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
101
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 47 publications
(111 citation statements)
references
References 32 publications
6
101
3
Order By: Relevance
“…Furthermore, LoCE lesions in the orbit, cavernous sinus, infratemporal fossa, and meninges were significantly associated with AIFRS-specific survival rate in univariate analysis but not in multivariate analysis. A recent multicenter study also reported that orbit and intracranial involvement were not statistically significant prognostic factors 16 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, LoCE lesions in the orbit, cavernous sinus, infratemporal fossa, and meninges were significantly associated with AIFRS-specific survival rate in univariate analysis but not in multivariate analysis. A recent multicenter study also reported that orbit and intracranial involvement were not statistically significant prognostic factors 16 .…”
Section: Discussionmentioning
confidence: 99%
“…We also found that there was no significant difference between the survival rate of invasive mucormycosis and that of aspergillosis. A recent multicenter study reported that atypical fungi, including Candida, Fusarium, and Alternaria, which are resistant to amphotericin B and other antifungal agents, were associated with poor survival rate 16 . Considering the efficacy of antifungal agents, our results may be because these organisms have individual susceptibilities to amphotericin B and voriconazole.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the 3 entities AIFS is certainly the most well described, and CGIFS seems to be geographically isolated to the Sudan, Pakistan, and India 2,5,6 . Numerous studies have described AIFS as that with an aggressive disease process and poor survivorship 17‐22 . Conversely, CIFS is less commonly described, has a seemingly indolent clinical course, and is without a known geographic pattern 1‐3,6 .…”
Section: Discussionmentioning
confidence: 99%
“…Adam Kaplon, BA 1 , Suraj Kedarisetty, MD 2 , and Caitlin McLean, MD 2 This case was institutional review board exempt according to Temple University protocol. A 58-year-old female with history of recurrent refractory chronic lymphocytic leukemia (CLL) on ibrutinib presented with one week of nasal congestion, rhinorrhea, and anosmia.…”
Section: Intranasal Herpes Simplex Virus (Hsv): a Unique Mimicker Of mentioning
confidence: 99%